2016
DOI: 10.1016/j.parint.2015.08.011
|View full text |Cite
|
Sign up to set email alerts
|

The in vivo trypanocidal effect of the diterpene 5-epi-icetexone obtained from Salvia gilliesii

Abstract: The search for new compounds with trypanocidal activity is crucial for the treatment of Chagas' disease. Previous in vitro studies have shown that the diterpene 5-epi-icetexone (ICTX) is active against Trypanosoma cruzi. The aim of this work was to evaluate the effect of ICTX on the parasites in infected mice, in an experimental model that mimics the acute phase of the disease. Swiss albino mice were infected with T. cruzi and treated daily with 10mg/kg/day ICTX (i.p.). Infected mice and mice injected with eit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 19 publications
0
10
0
Order By: Relevance
“…However, serratol (Schmidt et al ., ), hypoestenonols A/B (Al Musayeib et al ., ), and diterpenes from some Vietnamese corals (Thao et al ., ) were found to act against Trypanosoma brucei ). Additionally, a number of other diterpenes (Alves et al ., ; Freiburghaus et al ., ; Batista et al ., ; Scio et al ., ; Uchiyama et al , ; Torres‐Mendoza et al , ; Rubio et al ., ; González et al ., ; Sanchez et al ., ; Ambrósio et al ., ; Sartorelli et al ., ; Izumi et al ., ; Ramírez‐Macías et al ., ; Lozano et al ., ; Siless et al ., ; Bou et al ., ; Olmo et al ., ; Lozano et al ., ; Lozano et al ., ) are also reported to act against T. cruzi.…”
Section: Resultsmentioning
confidence: 99%
“…However, serratol (Schmidt et al ., ), hypoestenonols A/B (Al Musayeib et al ., ), and diterpenes from some Vietnamese corals (Thao et al ., ) were found to act against Trypanosoma brucei ). Additionally, a number of other diterpenes (Alves et al ., ; Freiburghaus et al ., ; Batista et al ., ; Scio et al ., ; Uchiyama et al , ; Torres‐Mendoza et al , ; Rubio et al ., ; González et al ., ; Sanchez et al ., ; Ambrósio et al ., ; Sartorelli et al ., ; Izumi et al ., ; Ramírez‐Macías et al ., ; Lozano et al ., ; Siless et al ., ; Bou et al ., ; Olmo et al ., ; Lozano et al ., ; Lozano et al ., ) are also reported to act against T. cruzi.…”
Section: Resultsmentioning
confidence: 99%
“…Other diterpenes, such as geranylgeraniol from Pterodon pubescens (Fabaceae), 6β-hydroxy-18-acetoxycassan-13,15-diene from Myrospermum frutescens (Fabaceae), cyclocoulterone and komaroviquinone from Dracocephalum komarovi (Lamiaceae), and 5epi-icetexone from Salvia gilliessi (Lamiaceae), have previously demonstrated potent activity on epimastigote forms of T. cruzi [22][23][24][25][26]. Abietane diterpenoids taxodione, ferruginol, 6-hydroxysalvinolone, and uncinatone from the roots of Clerodendrum eriophyllum (Verbenaceae) have shown significant activity against promastigote forms of the trypanosomatid Leishmania donovani, with IC 50 values of 0.1, 4.0, 3.2, and 0.2 µg/mL, respectively [27].…”
Section: Resultsmentioning
confidence: 99%
“…In animal models, it has been demonstrated that ICTX can protect mice from T. cruzi, at least during the early stages of infection (Fig. 11.10) (Lozano et al 2016).…”
Section: Effect Of Sesquiterpene Lactones and Diterpenes On Trypanosomentioning
confidence: 99%